(untitled) (International Journal of Language, Literacy and Translation, 2025)
Political cartoons constitute a specific genre of visual images. They are pictorial representations or attitudes with different cartoon elements which depict political and social issues, and events of a country, an institution or a party (Sani, Abdullah & Ali, 2014). Visual language as non-verbal communication may or may not be supported by a verbal text (Peñamarin, 1998). This paper sheds light on the themes of 29 selected Arab political cartoons as a sample that is widely spread during the Arab Spring era and its aftermath (Wo?niak, 2014). It also looks to identify the cartoon elements used by the cartoonists and to highlight the use of these elements such as colours, symbol, signs and others that connote different meanings. The study revealed that the visual language of Arab Spring cartoons from 2011 to 2013 reflected some common themes that highlight issues such as the image of democracy, the involvement of interfering countries and powers in the events of the Arab Spring, government authorities, military-people relations, the role of media and social media, an account of the stages of the Arab revolutions and issues of women's image in relation to socio-political change and ethical responsibilities for both the cartoonists and the Arab people. These are represented via visual messages that connote different meanings. It also revealed that the role of non-verbal visual language can be effectively realised and highlighted through the Arab cartoonists' utilisation of the interaction between different signs of the cartoons’ elements such as symbolism, metaphor, labelling, irony, analogy and colour to convey certain intended messages.